Hereditary Angioedema-Associated Acute Pancreatitis in C1-Inhibitor Deficient and Normal C1-Inhibitor Patients: Case Reports and Literature Review - Veronez, Camila Lopes; Campos, Régis Albuquerque; Constantino-Silva, Rosemeire Navickas; Nicolicht, Priscila; Pesquero, João Bosco; Grumach, Anete Sevciovic (Frontiers in Medicine, 2019)
Abdominal pain due to intestinal swellings is one of the most common manifestations in hereditary angioedema (HAE). Bowel swellings can cause severe abdominal pain, nausea, vomiting, and diarrhea, which may lead to misdiagnosis of gastrointestinal disorders. In rare cases, HAE abdominal attacks can be accompanied by acute pancreatitis. Here, we report 3 patients with HAE and acute pancreatitis and present a literature review of similar cases. Patients with confirmed diagnosis of HAE secondary to C1-inhibitor (C1-INH) deficiency (n=2) and HAE with normal C1-INH and F12 mutation (F12-HAE) (n=1) were included. Pancreatitis was diagnosed based on clinical symptoms and high lipase and amylase levels. Three HAE patients were diagnosed with acute pancreatitis based on increased amylase levels during severe abdominal swelling episodes. Two were previously diagnosed with HAE type I and one with F12-HAE. Pancreatitis was efficiently treated in two patients using Icatibant, with pain relief within hours. When conservatively treated, pancreatitis pain took longer time to resolve. Eighteen pancreatitis cases in HAE with C1-INH deficiency were previously reported and none in F12-HAE. Most patients (12/18) underwent invasive procedures and/or diagnostic methods. Although rare, severe abdominal HAE attacks could cause pancreatitis; HAE-specific treatments may be efficient for HAE-induced pancreatitis. HAE should be considered as a differential diagnosis of acute idiopathic pancreatitis. To our knowledge, this is the first report of HAE-induced pancreatitis in a F12-HAE patient treated with Icatibant.